2009
DOI: 10.1002/mabi.200800242
|View full text |Cite
|
Sign up to set email alerts
|

PAMAM Dendrimers as Potential Agents against Fibrillation ofα‐Synuclein, a Parkinson's Disease‐Related Protein

Abstract: The effect of PAMAM dendrimers (generations G3, G4 and G5) on the fibrillation of alpha-synuclein was examined by fluorescence and CD spectroscopy, TEM and SANS. PAMAM dendrimers inhibited fibrillation of alpha-synuclein and this effect increased both with generation number and PAMAM concentration. SANS showed structural changes in the formed aggregates of alpha-synuclein--from cylindrical to dense three-dimensional ones--as the PAMAM concentration increased, on account of the inhibitory effect. PAMAM also eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Another class of compounds exerting anti-aggregation effects includes polyamidoamine (PAMAM) dendrimers—highly branched polymers possessing a well-defined spherical geometry 109 . PAMAM dendrimers (generations G3, G4, and G5) inhibit fibrillization of α-synuclein and promote the breakdown of pre-existing fibrils.…”
Section: In Vitro Aggregation Assays Of α-Synucleinmentioning
confidence: 99%
“…Another class of compounds exerting anti-aggregation effects includes polyamidoamine (PAMAM) dendrimers—highly branched polymers possessing a well-defined spherical geometry 109 . PAMAM dendrimers (generations G3, G4, and G5) inhibit fibrillization of α-synuclein and promote the breakdown of pre-existing fibrils.…”
Section: In Vitro Aggregation Assays Of α-Synucleinmentioning
confidence: 99%
“…Rekas et al (2009) [124] observed the effect of PAMAM dendrimers (generations 3.0, 4.0 and 5.0) on the fibrillation of alpha-synuclein and found that PAMAM dendrimers suppressed the fibrillation and this effect was increased with both PAMAM concentration and generation number. They also found that as the PAMAM concentration increased there were structural changes in the formed aggregates of alpha-synuclein from cylindrical to dense three-dimensional ones.…”
Section: Treatment Strategies For Brain Diseases Using Dendrimersmentioning
confidence: 97%
“…PAMAM dendrimers (generations (G) 4, 5 and 6) used as purchased without modification were able to reduce ␣-synuclein fibrillation as measured by the Thioflavin T assay [238]. This occurred for all three generations, and the effect of concentration analyzed for G5 PAMAM showed a concentration dependence on the degree of inhibition.…”
Section: Polymeric Inhibitors Of Protein Aggregationmentioning
confidence: 99%